Studies of land surface temperature distribution using multispectral image Landsat - Hung, Trinh Le (Vietnam Journal of Earth Sciences, 2015)
Land surface temperature is one of the most important factors in urban climatology studies and human - environmentinteractions. Warmer air in urban area - urban heat island is a pressing issue for all big cities. Besides, land surfacetemperature is also an important factor when monitoring soil moisture. Ground-based observations reflect only thermalcondition of local area around the station and in fact cannot establish the number of meteorological stations withexpected density due to the high cost. Remote sensing technology with advantages such as wide area coverage andshort revisit interval has been used effectively in the study of land surface temperature distribution. The study indicateshow to estimate surface temperature using LANDSAT satellite data. With 120m (TM), 60m (ETM+) and 100m(LANDSAT 8) spatial resolution, thermal infrared image LANDSAT performance applications in the region study. Thisarticle also considers the method determining surface emissivity and building program LST for calculating land surfacetemperature. The land surface temperature distribution map and the analyses of thermal - land cover relationships canbe used as the reference for urban planning and the solution to the reduction of heat island effect.ReferencesAlipour T., Sarajian M.R., Esmaseily A., 2004. Land surface temperature estimation from thermal band of LANDSAT sensor, case study: Alashtar city. The international archives of the Photogrammetry, Remote sensing and Spatial information sciences, Vol. XXXVIII-4/C7. Balling R.C., Brazel S.W., 1988. High - resolution surface temperature patterns in a complex urban Terrain, Photogrametric engineering and Remote sensing, Vol. 54, No.9, pp. 1289 - 1293. Carnahan W.H., Larson R.C., 1990. An analysis of an urban heat sink. Remote sensing of Environment, 33:65 - 71. Fei Yuan, Marvin E. Bauer, 2007. Comparison of impervious surface area and normalized difference vegetation index as indicators of surface urban heat island effects in LANDSAT imagery. Remote sensing of Environment 106:375 - 386. Gallo K.P., Owen T.W., 1998. Satellite - Based adjustments for the urban heat island temperature bias, Journal of applied meteorology, Vol. 38, pp. 806 - 813. Garcia Cueto O.R., Jauregui Ostos E., Toudert D., Tejeda Martinez A., 2007. Detection of the urban heat island in Mexicali and its relationship with land use. Atmosfera 20(2), pp. 111 - 131. Holben B.N., 1986. Characteristics of maximum value composite image from temporal AVHRR data. International Journal of Remote sensing, 7:1417 - 1434. Hyung Moo Kim, Beob Kyun Kim, Kang Soo You, 2005. A statistic correlation analysis algorithm between land surface temperature and vegetation index, International journal of information processing systems, Vol. 1, No. 1, pp. 102 - 106. Javed Maltick, Yogesh Kant, D.B. Bharath, 2008. Estimation of land surface temperature -over Delhi using LANDSAT-7 ETM+”, Journal Ind. Geophys. Union, Vol. 12, No. 3, pp. 131 - 140. Lê Đình Quang, 2005. Sự hình thành đảo nhiệt ở nội thành thành phố Hà Nội. Tạp chí Khí tượng Thủy văn, 530, trang 44 - 46. Lo C.P., D.A. Quattochi, J.C. Luvall, 1997. Application of high resolution thermal infrared remote sensing and GIS to assess the urban heat island effect. International journal of Remote sensing, 18:287 - 304. Luke Howard, 1833. The climate of London. International association for urban climate (IAUC), 285p. Oke T.R., 1979. Technical note No. 169: Review of urban climatology. World meteorological organization, Geneva, Switzerland, 43p. Sundara Kumar K., Udaya Bhaskar P., Padmakumari K., 2012. Estimation of land surface temperature to study urban heat island effect using LANDSAT ETM+ image”, International journal of Engineering Science and technology, Vol. 4, No. 2, pp. 771 - 778. Tran H., Yasuoka Y., 2004. Surface Climatic impacts of Urbanization in the Hochiminh city, Vietnam: An intergrated study with remote sensing and modeling. Proceedings of the 3rd ICUS international symposium “New technologies for urban safety of megacities in Asia”, Agra, India, October 18 - 19. Tran Hung, Daisuke Uchihama, Shiro Ochi, Yoshifumi Yasuoka, 2006. Assessment with satellite data of the urban heat island effects in Asian mega cities. International journal of applied Earth observation and Geoinformation, Vol. 8, pp. 34 - 48. Trần Thị Vân, Hoàng Thái Lan, Lê Văn Trung, 2009. Phương pháp viễn thám nhiệt trong nghiên cứu phân bố nhiệt độ đô thị. Tạp chí Các Khoa học về Trái Đất, T.31, (2), trang 168 - 177. Valor E., Caselles V., 1996. Mapping land surface emissivity from NDVI. Application to European African and South American areas. Remote sensing of Environment, 57, pp. 167 - 184. Van de Griend A.A., Owen M., 1993. On the relationship between thermal emissivity and the normalized difference vegetation index for natural surface. International journal of remote sensing 14, pp. 1119 - 1131. LANDSAT Conversion to Radiance, Reflectance and At-Satellite Brightness Temperature (NASA).